“O Pão Nosso de Cada Dia” (1978): as materialidades simbólicas da resistência cotidiana na obra de Anna Bella Geiger - Andrade, Camila de Souza Lima de (2022)
In Brazil, from the 60s onwards, between the contestations of counterculture, social movements and themilitary dictatorship, artistic proposals turned to productions and narratives that had as their theme politics, culture, the body, otherness and others aspects of everyday life. Artists sought to break with art without engagement and brought creations based on new technologies that were accessible at the time,trying to subvert contemporary languages. In this scenario, the Brazilian artist Anna Bella Geiger standsout, whose works bring issues of identity, sócio-political representation and denunciation of theauthoritarianism of the historical moment in which the country and Latin America were passing through. The objective of this research is to understand how Geiger uses in his work “O Pão Nosso de Cada Dia” (1978), the materialities, techniques and technologies, to question and give new meaning to cultural, social, political and everyday systems. Garcia Canclini (1997) states that the ideas of the aesthetic avant-gardes and modern art did not problematize politics and the need to change the social scenario,as the market system was very repressed. Artists sought ways to fight against this standardized and linear artistic current, making manifestos and experiments, not crystallizing the styles and “isms” globalized by the political and social market. Authors such as Garcia Canclini and Stuart Hall help to understand the relationships between art and culture, identity, representation and new technological mediations in the construction of a more democratic and egalitarian world. The research intends to reflect on the trajectory of Anna Bella Geiger and the way in which her works interrogate the borders, the geopolitical limits, giving new meaning, especially with “O Pão Nosso de Cada Dia” (1978), the daily life and the Brazilian society.